Traditional plant uses and medicinal significance in Western Nepal: A study of Ramaroshan rural municipality, Achham district - Neupane, Sanju; Thapa Magar, Gyanu; Chaudhary, Sujan; Pant, Deepak (Ethnobotany Research and Applications, 2025)
Background: Indigenous and local communities of diverse origins in Nepal have used medicinal plants for primary healthcare since time immemorial. This study aims to document traditional plant-use knowledge across various categories in Ramaroshan rural municipality, Western Nepal. Methods: Data were collected through informant interviews and focus group discussions using semi-structured questionnaires. A linear regression was performed to observe the relationship between the age of respondents and the number of plants described by them. The quantitative data were analyzed to calculate Use Values (UV), Informant Consensus Factor (ICF), and Fidelity Level (FL) across different plant use categories and ailments. Results: A total of 155 plant species, 136 genera and 70 families were reported. The plants were categorized according to their uses as food, medicine, fodder, handicrafts, timber, and religious/cultural values. Among the different groups of plant, the angiosperms especially the herbs were the most commonly used plants, and the leaves were the most commonly used plant parts, for the livelihood in local traditions. The Fidelity Level (FL) identified Taxus sp. and Ageratina adenophora, among others, as highly specialized plants for cancer and skin disorders. Conclusions: Ethnobotanical plants play a vital role in sustaining the livelihoods of rural communities. This study offers a comprehensive documentation of plant species utilized by the Khas community in Ramaroshan rural municipality, Achham District. The findings highlight the urgent need to conserve biodiversity and its associated traditional knowledge, which could also pave the way for future scientific research. Keywords: Khas community, Traditional knowledge, Fidelity level, Knowledge transfer, West Nepal